Progressive cribriform and zosteriform hyperpigmentation - Rameshwar M Gutte (Wolters Kluwer Medknow Publications, 2014)
Here we report a case of a healthy 30-year-old male who presented to us with progressively increasing reticulate pigmented lesions following lines of Blaschko on the right side of abdomen and back. Skin biopsy revealed increased basal layer pigmentation without nevus cells. A diagnosis of progressive cribriform and zosteriform hyperpigmentation (PCZH) was made on clinicopathological correlation. We also discuss clinicopathological differentials of this peculiar pigmentary disorder.